Relationship between Illness Perception and Depressive Symptoms among Type 2 Diabetes Mellitus Patients in China: A Mediating Role of Coping Style. (16th October 2020) - Li, Jiarui; Qiu, Xiaohui; Yang, Xiuxian; Zhou, Jiawei; Zhu, Xiongzhao; Zhao, Erying; Qiao, Zhengxue; Yang, Yanjie; Cao, Depin
Abstract : Objective . The aims of the present study were to investigate the prevalence of depressive symptoms among type 2 diabetes mellitus (T2DM) patients in China and to explore how coping style influences the relationship between illness perception and depressive symptoms. Methods . Nine hundred and thirty-nine T2DM patients were recruited from a grade 3 Class A hospital in Harbin, China, and asked to complete a demographic questionnaire as well as the Self-rating Depression Scale (SDS), Brief Illness Perception Questionnaire-Revised (IPQ-R), and Medical Coping Modes Questionnaire (MCMQ). Hierarchical linear regression analysis and the bootstrap method were preformed to examine if coping style influenced the relationship between illness perception and depression. Results . The majority of patients (73.59%) exhibited depressive symptoms, including 37.27% with moderate and 6.71% with severe depressive symptoms. Depressive symptoms were more frequent in patients with complications (P < 0.05 ). A resignation coping style partially mediated the influence of illness perception on depressive symptoms. Conclusions . Interventions to improve coping style may reduce the prevalence or severity of depressive symptoms among T2DM patients, potentially enhancing treatment adherence and clinical outcome.